Harmonics estimator design with Trigonometric function inspired Grey Wolf Optimiser. (20th January 2023) - Mehta, Aishwarya; Jangid, Jitesh; Saxena, Akash; Shekhawat, Shalini; Kumar, Rajesh
The harmonic estimator design problem is more meaningful in the emerging power systems as quality of power is closely interlinked with consumer satisfaction and electricity price. For designing estimators, bio-inspired algorithms have been employed by researchers. This paper addresses the problem of estimating harmonic components in terms of phase and amplitude of complex waves. Although, for accurate identification of harmonics, several methods have been proposed, yet metaheuristic-based approaches have been used and in practice since the last two decades. Taking inspiration from these, the work presented in the manuscript is a proposal for a harmonic estimator design based on proposed Trigonometric function inspired Grey Wolf Optimiser (T-GWO). To validate the performance of T-GWO, we tested the proposed variant on conventional benches and then a harmonic estimator design is executed. We can observe the satisfactory performance of T-GWO as compared with the other state-of-the-art approaches existed in literature.